BUDAYA BERBAGI PENGETAHUAN TERHADAP KINERJA : MENGUJI EFEK MEDIASI KETERLIBATAN KARYAWAN DI BAWASLU KABUPATEN JEPARA - Ismanto, Ngari; Mahfudh, Ainul; Roosdhani, Mohamad Rifqy; Arifin, Samsul (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This study was conducted to examine the culture of knowledge sharing in Bawaslu Jepara on performance mediated by employee involvement. Bawaslu employees in Jepara district as many as 316 people became the population of the study, consisting of 20 Jepara Bawaslu employees, 156 Panwascam and staff and 185 Village / kelurahan Election Supervisory Committees. The sample in this study amounted to 163 people as a result of the Slovin Formula calculation. Structural Equation Modeling-Partial Least Square (SEM-PLS) was used for data analysis, namely testing the connectivity between independent-dependent variables in the study. the research conducted an analysis to test the validity and reliability of the questionnaire used and multiple linear analysis for hypothesis testing. The results of the study prove that knowledge sharing culture has an influence on employee performance, but the effect is not significant. Other evidence reveals if knowledge sharing culture has a positive effect on employee involvement in the process of running the organization, employee involvement affects performance and a significant influence is obtained between knowledge sharing culture on employee performance with employee involvement as an intervening variable. Keywords: Employee trust, Knowledge Sharing Culture, Employee Performance